Pothole Distress Assessment Innovation on the Surface of the Asphalt Pavement - Abu Bakar, Muhammad Naim; Ambak, Kamarudin (Recent Trends in Civil Engineering and Built Environment, 2024)
A persistent issue in Malaysia for asphalt pavement distresses are cracks and potholes which are affecting a wide range of stakeholders, including those responsible, such as the Public Works Department (JKR) and concessionaires. The purpose of this study is to see how effective application or recommendation software is at detecting distresses and making repair recommendations for cracks and potholes in asphalt pavements. The visual assessment method is carried out through the user interface system's features of user information extraction and potholes distresses, as well as by the sensory infrastructure in the background of this application system through its use. This application was built on the Mit App Inventor platform. The analysis findings will show user data, the severity of the distresses, and a proposal to repair the pavement distress to the on-site inspection officer based on the Public Works Department's (JKR) Malaysia's standard treatment methods. Pavement distress analysis using automated digital image evaluation techniques can speed up the process of obtaining analyzed data, reducing the risk of accidents and costs. Furthermore, mobile phone-based automated visual assessment methods improve the objectivity, accuracy, and consistency of pavement distress survey data. As a result,the proposed system for improving pavement distress assessment is to develop automated assessment innovations so that pavements can be better and more efficiently analyzed, as well as to help increase the age range of pavements byrecommending appropriate repair proposals based on the severity of pavement distress.